Local Demands of forest Produce and Working Plan (A Case Study of Vyara forest Division in Gujarat) - Verma, A. K. (Indian Forester, 2001)
National Forest Policy, 1988 recognises the dependence of the forest dwelling population and other poor living within and near forests, on the local forest resouree and prescribes and their domestic requirements of Fuelwood, Fodder, Minor Forest Produce and construction timber should be the first charge on forest produce. It is therefore necessary to estimate local demand of forest produce quantitatively while preparing or revising the Working Plan/ Management Plan of a forest area. The estimation would affect the quantity and quality of removals from the forest as well as guide the management prescriptions influencing species composition, rotation, harvesting regime and even cultural and tending operations. In this paper local requirement of forest produce in Vyara Forcst Division area of Gujarat has been estimated on the basis of primary data collected through sample survey and secondary information available from existing reliable data base. It has been found that the area is self sufficient, so far as local demands of timber is concerned. However large demand-supply gap exists in case of firewood even in the well-wooded localities. The gap can be bridged up by increasing firewood productivity, maximising fuelwood efficiency and using substitutes of firewood. Increase ill fuel wood and MFP giving species in the plantation, expansion of social forestry and JFM, delay in harvesting timber, installation of solar cooker, improved crematoria, improved earthen hearths and biogas plants, subsidised distribution of LPG in forested tracts and large scale awareness campaign have been recommended as methods for narrowing the demand supply gap of forest produce.